Infrastructure and Safety in a Collaborative World Road Traffic Safety - Bekiaris, Evangelos; Wiethoff, Marion; Gaitanidou, Evangelia; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
The book investigates how, and which, forgiving road environments (FOR) and self-explaining road measures (SER) will contribute to increasing road safety and also increase network efficiency on the road. It presents both the general approach and the methodology for generating the possible FOR and SER measures. The book further discusses the prioritization and the testing methodologies, as well as an innovating methodology for VMS methodology. The next parts of the book present a few important cases: lane departure warning systems; intelligent speed adaptation systems and perception enhancement studies; designs of European pictorial signs, e.g. for VMS but also examples of designs of European road wordings; and finally how personalization can be affectively applied in VMS signs and wordings for improving safety on the road and drivers comfort. The last part shows the final evaluation of FOR and SER, on a number of detailed Multiple Criterion Analysis and Cost Benefit Analyses are performed on a number of FOR and SER measures. This results in the development of a set of guidelines, conclusions and policy recommendations for the future. It is thus a book for the road safety researcher practitioner, the vehicles and road infrastructure components designer, the road operator, the local and national road authorities and -last but not least- for the informed citizen.
Europe at the crossroad -- From accidents to measures -- Towards forgiving and self-explanatory roads -- Structuring the way -- A bundle of ideas -- Drawing the picture -- Models on the road -- Planning ahead -- Managing the risk -- Back to school -- Staying in line -- Easy going -- Look and see? - Without words -- A European road dialect -- As you like IT -- Best things first -- Value for money -- Anybody listening -- Our future.
Electronic reproduction.
Keywords: Traffic safety; Electronic book